The Role of Insulin Resistance in Diabetic Patients with Chronic Liver Disease - Neneng Ratnasari; Siti Nurdjanah; Putut Bayupurnama; Sutanto Maduseno (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Background: The association between diabetes and chronic liver disease has been well documented. However, the mechanism remains unknown. The aim of this study was to investigate the insulin resistance in chronic liver disease and normal liver in diabetic patient. Method: A total of 31 diabetic, non-alcoholic patients with multiple oral hypoglycemic drugs, either with or without lipid abnormalities were enrolled in this study. Subjects were recruited from outpatient clinic of Department of Endocrine at Dr. Sardjito Hospital, Jogjakarta, Indonesia from May-June 2004. This was a cross sectional study. Fasting insulin and glucose level, liver function test, body mass index, and the presence of fatty liver by ultrasound were examined. Insulin resistance was estimated by calculating fasting insulin and glucose plasma level as the homeostasis model assessment (HOMA) index ratio. Data was described with mean ± SD and analyzed by independent sample t-test. Results: Thirty one patients were enrolled to the study, i.e. 8 patients with normal liver and 23 patients with fatty liver. Only 14 patients agreed to continue the study including 10 patients with fatty liver and 4 patients with normal liver. Mean of age was 59.1 ± 8.7 and mean value of BMI was 24.62 ± 3.05. The liver function test revealed normal Results. Triglyceride, cholesterol, fasting glucose level, and HOMA index (2.77 ± 1.95 vs. 1.66 ± 1.02) in patients with fatty liver were higher than patients with normal liver. No correlation was found between fasting insulin level as well as HOMA index and mean value of BMI (obese and non-obese) as well as hypertension. There was significant correlation between triglyceride level and fasting insulin among fatty liver patients (p = 0.048; CI 95% -7.404; -0.032). Conclusion: The non-alcoholic fatty liver disease in diabetic patients with normal liver enzymes and multiple oral hypoglycemic drugs appear to be related with insulin resistance and hypertriglyceridemia. Keywords: fatty liver, diabetic, insulin resistance